EFEK PENAMBAHAN EKSTRAK KAYU SECANG (Caesalpinia sappan L.) DAN MINYAK IKAN LEMURU DALAM RANSUM PAKAN TERHADAP HEN DAY PRODUCTION, KONVERSI PAKAN, DAN MORTALITAS PUYUH PETELUR - Anang Widigdyo; Adiguna Sasama Wahyu Utama (Universitas Islam Balitar, 2020)
The purpose of this study was to evaluate the effect of giving levels of secang wood extract and lemuru fish oil on the appearance of laying quails which included feed consumption, Hen Day Production (HDP), feed conversion of quail egg mortality. This study used Autumn strain quail with a population of 168 individuals with basal feed supplemented with several levels of secang wood extract. This research method is an experiment using a completely randomized design (CRD) factorial with 4 treatments with 6 replications with each repetition consisting of 7 quails aged 10-15 weeks. The treatment was as follows: P0 = basal feed without the addition of secang wood extract P1 = basal feed + 0.2% EKS + 4% MIL, P2 = basal feed + 0.4% EKS + 4% MIL, P3 = basal feed + 0 , 6% EX + 4% MIL. The addition of a combination of secang wood extract and fish oil was carried out according to the level of quail feeding. The variable being measured; feed consumption, Hen Day Production (HDP), Feed conversion, mortality. Addition of secang wood extract with a level of 0%; 0.2%; 0.4%; 0.6%, and 4% lemuru fish oil had no significant effect on feed consumption, hen day production, feed conversion, mortality, this was due to flavonoids, polyphenols and active compounds in oil. lemuru fish does not affect the appearance of quail egg production. Flavonoid compounds in low concentrations have no effect on chicken feed consumption, because the content of flavonoid compounds can still be tolerated by the chicken body. The use of lemuru fish oil with a concentration of up to 6% in quails does not affect the consumption of quail feed, because the addition of lemuru fish oil does not affect the palatability of quail feed. The conclusion of this study was that the addition of secang wood extract. The addition of secang wood extract and lemuru fish oil did not affect hen day production, feed conversion and mortality of laying quails